Growth and physiological responses of the halophyte Salicornia ramosissima to CO2 enrichment and salinity - Perez Romero, Jesus Alberto (2017)
Climate change emerges as one of the biggest challenges for sustaining global food security so it is crucial to research about alternative crops; species capable of growing in hostile environments (salinity and water deficit). In this respect halophyte plants, like Salicornia ramosissima, may be considered because they possess morphological and physiological traits that allow them to survive against rough conditions. A glasshouse experiment was design to study the growth and physiological response of the halophyte Salicornia ramosissima, selected for its commercial interests as practical crop, in synergistic conditions of elevated CO2 (400 and 700 ppm) and salinity (0, 171, 510 mM NaCl). Gas exchange, efficiency of PSII, photosynthetic pigments profiles, carbon isotopic discrimination and antioxidant enzymatic activity were measure to follow the physiological state of the plants. Our results revealed that S. ramosissima was able to maintain its growth even at salinities of 510 mM NaCl or 700 ppm of CO2, since there was no significant difference between any treatments in the relative growth rate, RGR, although it was lower at 0 mM NaCl. Also, our preliminary results showed a positive effect on S. ramosissima development at 700 ppm CO2, in terms of enhancement of chlorophyll a and b concentrations and modulation of its antioxidant enzymatic activity which was showed by the superoxide dismutase.